1996
DOI: 10.1074/jbc.271.26.15478
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Calcium Channel Currents Underlie Defective Insulin Secretion in a Transgenic Mouse

Abstract: A transgenic mouse overexpressing a mutant form of calmodulin (CaM-8) that is selectively targeted to pancreatic beta-cells has an impaired ability to secrete insulin in response to elevated blood glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The Ca 2ϩ channels affected by the CaM-8 mutation are the L-type Ca 2ϩ channels because dihydropyridines blocked these currents (50). It is of interest that previous patch clamp studies using GH3 pituitary cells stably transfected with calbindin found that calbindin reduces Ca 2ϩ influx through voltage dependent L-type Ca 2ϩ channels (51).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Ca 2ϩ channels affected by the CaM-8 mutation are the L-type Ca 2ϩ channels because dihydropyridines blocked these currents (50). It is of interest that previous patch clamp studies using GH3 pituitary cells stably transfected with calbindin found that calbindin reduces Ca 2ϩ influx through voltage dependent L-type Ca 2ϩ channels (51).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies were done on another mouse transgenic line, referred to as CaM-8. CaM-8 expresses in its ␤ cells a mutant form of calmodulin that is functionally similar to calbindin because it binds calcium with high affinity, and, unlike calmodulin but similar to calbindin, it does not activate effector proteins such as protein phosphatases and kinases (49,50). The CaM-8 transgenic mice also display defective insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ankyrin G also associates with skeletal muscle postsynaptic membranes and sarcoplasmic reticulum (38), and CaMKII participates in regulating local [Ca 2ϩ ] gradients in subcellular zones involved in Ca 2ϩ signaling. CaMKII is an important Ca 2ϩ signaling effector and serves as a gauge that temporally integrates [Ca 2ϩ ] signal intensities (39), and calmodulin participates in several Ca 2ϩ -dependent processes in insulin secretion by ␤-cells (40,41). Calmodulin and iPLA 2 ␤ interact functionally (2,8,23,24,33), and the iPLA 2 ␤ domain from residues 650 -722 contains a calmodulin binding site (2).…”
mentioning
confidence: 99%